Correlation between maternal and umbilical cord 25-hydroxy-vitamin D levels over a range of values. A prospective observational study from the United Arab Emirates. - Magnus Jutell; Shakura Bhat; Maria Lindstrom Bagge; Per-Erik Isberg; Nana Wiberg (PLoS ONE, 2024)
Worldwide vitamin D insufficiency is remarkably prevalent in both children and adults, including pregnant women. The total amount of the vitamin is best measured by 25-hydroxy-vitamin D (25(OH)D), which is a measurement of total serum cholecalciferol 25(OH)D3 and ergocalciferol 25(OH)D2. There is a known correlation between maternal and umbilical cord blood (UCB) 25(OH)D; however, whether specific maternal demographics or comorbidities influence the correlation remains uncertain. This prospective observational study was designed to study if maternal 25(OH)D levels, maternal age and BMI, amount of supplementation, mode of delivery, diabetes, hypertension/preeclampsia, or sunlight exposure had an impact on the correlation. Women were enrolled in the study at admission to the labor ward. If they agreed to participate, venous blood was directly collected and analyzed for 25(OH)D. The UCB was sampled after delivery from the unclamped cord and immediately analyzed for 25(OH)D. ANOVA, Fisher's exact test, Pearson's correlation, and test of the differences between correlations using Fisher's z-transformation with Bonferroni correction were used accordingly. Of the 298 women enrolled, blood from both the mother and umbilical cord was analyzed successfully for 25(OH)D in 235 cases. The crude correlation between maternal and UCB 25(OH)D was very strong over all values of 25(OH)D (r = 0.905, R2 = 0.821, p <0,001) and remained strong independently of maternal demographics or co-morbidities (r ≥ 0.803, R2 ≥ 0.644, p <0.001). For women who delivered by caesarean section in second stage the correlation was strong (r ≥ 0.633, R2 ≥ 0.4, p <0.037). Test of differences between correlations showed significant stronger correlation in women with unknown 25(OH)D3 supplementation compared to women receiving 10.000 IU/week (p = 0.02) and 20.000IU/week (p = 0.01) and that the correlation was significantly stronger for women with a BMI of 25-29.9 compared to women with a BMI of <24.9 (p = 0.004) and 30-34.9 (p = 0.002). 213 (91%) women had lower 25(OH)D compared to the neonate, with a mean difference of -13.7nmol/L (SD = 15.6). In summary, the correlation between maternal and UCB 25(OH)D is very strong throughout low to high maternal levels of 25(OH)D with lower levels in maternal blood. Typical maternal demographics and comorbidities did not affect the transition.